Consumption‐Based Emissions of African Countries: An Analysis of Decoupling Dynamics and Drivers - Jieyu Wang; Yuli Shan; Jinghang Xu; Ruoqi Li; Congyu Zhao; Shaojian Wang (Earth's Future)
Abstract Formulating equitable climate policies should not overlook the challenges faced by less developed regions. African countries are at a crucial stage of economic development and deeper integration into global trade. Therefore, understanding their carbon footprints (i.e., consumption‐based CO2 emissions) is essential for crafting a sustainable development pathway for Africa and developing comprehensive and fair climate policies. Here, we investigate consumption‐based CO2 emissions in 55 African economics using a new Multi‐Regional Input‐Output model called “EMERGING” for 2015–2019; we also analyze the impacts of global trade participation on emissions, the decoupling status of emissions and economic, and hidden influencing factors. Results show that 65% of African countries experienced rapid growth in consumption‐based emissions, with an average annual growth rate of 6.4%. Significantly, 87% of African countries are net emissions importers, predominantly attributed to their trade relations with other developing countries (i.e., South‐South trade), a condition characterizing 68% of all trade interactions; The embodied carbon in imports is primarily concentrated in the transportation, petroleum refining, metal products, and machinery sectors. The decoupling analysis indicates that 15 countries strongly decoupled from production‐based carbon emissions, and 14 from consumption‐based; however, only 9 have concurrently achieved decoupling in both domains of emissions. Optimizing the carbon emission efficiency of final demand, particularly within the tertiary sector, is a key for successful decoupling and emissions reduction. The findings provide essential insights from consumption‐based emissions that could guide more effective, targeted climate policies contributing to the mitigation of climate impacts and fostering sustainable development in African nations.